Response Characteristics of Steppe Inland River Basins under Climate Change and Its Impact on Runoff from 1982—2020 - CHEN Hongguang; MENG Fanhao; SA Chula; LUO Min; WANG Mulan (Renmin Zhujiang)
Based on hydro-meteorological data and normalized difference vegetation index (NDVI) from 1982 to 2020,this paper studies the Wulagai River basin in Inner Mongolia and analyzes the vegetation response characteristics of the basin under climate change and its impact on runoff by adopting a hydrological model of soil and water assessment tool (SWAT) and statistical analysis method.The results show that the SWAT model has good applicability in the basin.The Nash-Sutcliffe efficiency coefficient (NSE) and coefficient of determination (R2) are larger than 0.62 in both regular and validation periods,and the relative error (PBLAS) is less than 18.8%.In the last 40 years,precipitation in the basin decreased slowly at a rate of 8.9 mm/10a,while temperature and actual evapotranspiration increased at a rate of 0.43°C/10a and 2.8 mm/10a,respectively,which indicates that the basin is becoming warm and dry.As the basin climate gets warm and dry,the vegetation recovers and grows vigorously.As a result,climate change and vegetation recovery lead to a reduced runoff depth of the basin.The study results can provide a reference for ecological conservation and sustainable utilization of water resources of inland river basins in arid and semi-arid regions.